Role of nitric oxide in thermotolerance - Zhao, Liqun (Landes Bioscience, 2010)
A tCaM3 is a key factor in heat shock (HS) signal transduction. Nitric oxide (NO) is believed to mediate a variety of resistant reactions against environmental factors. Our experiments indicate that under heat stress NO induces thermotolerance. In order to do so, NO is signal molecule acting upstream of AtCaM3, stimulating the DNA-binding activity of HS transcription factors as well as the accumulation of heat shock proteins. As a novel HS signaling molecule, NO signal pathway is little known and several unexpected results are emerging. Herein we are discussing them and conclude that in order to obtain a more profound understanding of this new role of NO, detailed research will be needed in the future.